Guselkumab Retention, Effectiveness, and Safety in Psoriasis: A 260-Week Real-World Multicenter Retrospective Study Exploring the Role of Concomitant PsA–IL PSO (Italian Landscape Psoriasis) - Mario Valenti; Luciano Ibba; Sara Di Giulio; Paolo Dapavo; Piergiorgio Malagoli; Angelo V. Marzano; Francesco Loconsole; Martina Burlando; Anna Balato; Valentina Dini; Matteo Megna; Giampiero Girolomoni; et al. (Dermatology and Therapy)
Abstract Introduction Guselkumab is a monoclonal antibody targeting the p19 subunit of interleukin (IL)-23, approved for the treatment of moderate-to-severe plaque psoriasis and psoriatic arthritis (PsA). While patients with psoriasis often achieve high clinical response rates (Psoriasis Area and Severity Index [PASI] 90 and PASI 100), the presence of PsA may influence long-term outcomes. We conducted a 260-week, multicenter, retrospective study to compare the effectiveness, safety, and drug survival of guselkumab in patients with and without concomitant PsA. Methods A total of 1765 patients were enrolled, including 352 with a concomitant diagnosis of PsA and 1413 with isolated skin involvement. All patients were treated with guselkumab following the approved dosing schedule for moderate-to-severe plaque psoriasis for at least 1 year. Treatment effectiveness was evaluated in terms of PASI 90, PASI 100, and absolute PASI ≤ 2 at weeks 16, 28, 52, 104, 156, 204, and 260. Guselkumab drug survival was assessed using the Kaplan–Meier method at the same time points. The safety profile was evaluated by analyzing adverse events recorded in medical charts at each follow-up visit. Results Throughout the study period, response rates remained comparable between the two cohorts of patients, with a significant difference at 2 years of follow-up in terms of PASI 90 (80.51% versus 74.02%). Drug survival overall remained stable and similar, with 79.5% (95% confidence interval (CI) 76.9–81.9) of patients without PsA and 78.5% (95% CI 72.9–83.1) of patients with PsA still receiving guselkumab treatment after 5 years. Conclusions Our results confirm the long-term effectiveness, persistence, and favorable safety profile of guselkumab in patients with moderate-to-severe psoriasis, regardless of the presence of concomitant PsA.